Inhibition of Drp1/Fis1 interaction slows progression of amyotrophic lateral sclerosis. Issue 3 (15th January 2018) - Joshi, Amit U; Saw, Nay L; Vogel, Hannes; Cunnigham, Anna D; Shamloo, Mehrdad; Mochly‐Rosen, Daria
Abstract: Bioenergetic failure and oxidative stress are common pathological hallmarks of amyotrophic lateral sclerosis (ALS), but whether these could be targeted effectively for novel therapeutic intervention needs to be determined. One of the reported contributors to ALS pathology is mitochondrial dysfunction associated with excessive mitochondrial fission and fragmentation, which is predominantly mediated by Drp1 hyperactivation. Here, we determined whether inhibition of excessive fission by inhibiting Drp1/Fis1 interaction affects disease progression. We observed mitochondrial excessive fragmentation and dysfunction in several familial forms of ALS patient‐derived fibroblasts as well as in cultured motor neurons expressing SOD1 mutant. In both cell models, inhibition of Drp1/Fis1 interaction by a selective peptide inhibitor, P110, led to a significant reduction in reactive oxygen species levels, and to improvement in mitochondrial structure and functions. Sustained treatment of mice expressing G93A SOD1 mutation with P110, beginning at the onset of disease symptoms at day 90, produced an improvement in motor performance and survival, suggesting that Drp1 hyperactivation may be an attractive target in the treatment of ALS patients. Synopsis: Drp1 hyperactivation has been associated with neurodegenerative diseases, like amyotrophic lateral sclerosis (ALS). P110, an inhibitor of the mitochondrial fission protein Drp1, is shown to reduce the detrimental effects of mitochondrial dysfunction and ameliorate symptoms in an ALS mouse model. P110 suppresses mitochondrial dysfunction in patient‐derived fibroblasts, SOD1 G93A NSC‐34 cells and in ALS model mice. P110 reduces muscular mitochondrial pathology and oxidative stress in ALS model mice. P110 enhances motor activity in ALS model mice. Drugs that improve mitochondrial function, such as P110, may provide benefits for patients with motor neuron diseases that show mitochondrial defects. Abstract : Drp1 hyperactivation has been associated with neurodegenerative diseases, like amyotrophic lateral sclerosis (ALS). P110, an inhibitor of the mitochondrial fission protein Drp1, is shown to reduce the detrimental effects of mitochondrial dysfunction and ameliorate symptoms in an ALS mouse model.